NOMADIC IMPACT ON THE LATE ANTIQUE BOSPORAN STRATEGY - Alekseevich Astakhov, Ivan (Revista Inclusiones, 2020)
The Bosporan Kingdom throughout its existence was in close proximity to various nomadic societies of antiquity. Late antiquity was for the Bosporus not only a period of difficult economic, social, internal and foreign policy crises, but also a period of active “barbarization”. The influence of the tribes, which the Migration Period “threw out” in the steppes of the Northern Black Sea Region, on the ancient society of the Bosporus was enormous. Barbarization was expressed in ethnic mixing, as well as material and technical borrowing. Nomads of the Northern Black Sea Region, being representatives of a unique culture, undoubtedly took an active part in this process. However, could they not only bring to the military affairs of the Bosporus technical innovations, but also modify the very principles of warfare? To answer this question, one needs to understand what the strategic thought of a nomadic army was.